2008
DOI: 10.1345/aph.1l129
|View full text |Cite
|
Sign up to set email alerts
|

Sibutramine-Associated QT Interval Prolongation and Cardiac Arrest

Abstract: Clinicians prescribing sibutramine should monitor their patients for ECG abnormalities and be cautious in coprescribing drugs known to prolong the QT interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Further studies are required, but sibutramine should be avoided in patients with long QT syndrome and in patients taking other medicines that may prolong the QT interval (35). Another article (36) reported on a probable association between sibutramine and QT interval prolongation leading to ventricular fibrillation and cardiac arrest in a 51-year-old woman with obesity but no other relevant past medical history or cardiac risk factors. Therefore sibutramine should be avoided by patients with high susceptibility for cardiac arrhythmia.…”
Section: Sibutramine and Case Reports Of Cvd Adverse Eventsmentioning
confidence: 99%
“…Further studies are required, but sibutramine should be avoided in patients with long QT syndrome and in patients taking other medicines that may prolong the QT interval (35). Another article (36) reported on a probable association between sibutramine and QT interval prolongation leading to ventricular fibrillation and cardiac arrest in a 51-year-old woman with obesity but no other relevant past medical history or cardiac risk factors. Therefore sibutramine should be avoided by patients with high susceptibility for cardiac arrhythmia.…”
Section: Sibutramine and Case Reports Of Cvd Adverse Eventsmentioning
confidence: 99%
“…[89] Another paper reported on a probable association between sibutramine and QT interval prolongation leading to ventricular fibrillation and cardiac arrest in a 51-year-old woman with obesity but no other relevant past medical history or cardiac risk factors. [90] In vitro studies demonstrated that sibutramine preferentially inhibits the hERG potassium channel, in a concentration-dependent manner, an effect that may contribute to prolong the cardiac action potential duration associated with long QT syndrome. [91] Therefore sibutramine should be avoided by patients with high susceptibility for cardiac arrhythmia.…”
Section: -Recent Case Reports Of Arrhythmia or Acute Myocardial Infarmentioning
confidence: 99%
“…There are two previously published reports of sibutramine‐induced cardiac arrest, but in both cases, sibutramine was prescribed for 1–4 months to treat obesity before the cardiac arrest 4, 5. In the reported cases4, 5 and also the present patient, the QT interval was significantly prolonged at admission and was normalized after discontinuation of sibutramine. The significant impact of this agent on ventricular repolarization, that is, significant increase in QT dispersion, was shown in 65 consecutive patients 6.…”
Section: Discussionmentioning
confidence: 51%